Disciplinary Borders and Borrowings: Social Work Knowledge and its Social Reach, a Historical Perspective. - Adrienne Chambon (Social Work and Society)
The relevance of outside boundaries and borrowings is one entry point into a discussion on the nature of a discipline and the identity of a field. The activities at the borders of a field are concrete manifestations of movements in knowledge in the academic sense (academic location and mandate), and express ways in which members of the field relate to broader social relations (responsiveness and agency in the societal order of relations.)